Enpowerment Strategy of Kandri Tourism Village Through Technology Information Media - Umi Hanifah; Bayu Tri cahya; Miftah Nurul Khaqiqi; Fitri Handayani (Proceeding of International Conference on Science, Health, And Technology, 2021)
Tourism is a sector that plays an important role in improving the economy of a country. One of the efforts to empower people living in rural areas is through the tourism sector because the potential tourism in Indonesia is in rural areas. The purpose of this article is to reveal how the economic conditions of the Kandri village community are and how the community empowerment strategy to form a tourism village. This research was conducted in Kandri Village, Gunungpati District, Semarang Regency. This research uses qualitative methods by collecting data based on interviews, observation and documentation. The approach in this study uses the phenomenology approach. The results showed an increase in income among the people of Kandri Village after being turned into a Kandri Tourism Village, then in terms of facilities there were also improvements that supported the comfort of the visitors. In terms of analysis, namely Strengths, it can be seen that the management of tourism in Kandri Village is completely handled by the Kandri Village manager through the media of information technology. Weaknesses (Weaknesses) in tourism management is that direct tourism management is still carried out by people who live in tourism objects, while in terms of Opportunities (opportunities) there are the many potential tourist objects in Semarang Regency as regional tourism development. Threats are the changing of policies for the implementation of activities, so that the implementation of activities does not run effectively.